Negative impact of COVID-19 pandemic on sleep quantitative parameters, quality, and circadian alignment - Salehinejad, Mohammad Ali; Majidinezhad, Maryam; Ghanavati, Elham; Kouestanian, Sahar; Vicario, Carmelo M.; Nitsche, Michael A.; Nejati, Vahid (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
The COVID-19 pandemic has spread worldwide, affecting millions of people and exposing them to home quarantine, isolation, and social distancing. While recent reports showed increased distress and depressive/anxiety state related to COVID-19 crisis, we investigated how home quarantine affected sleep parameters in healthy individuals. 160 healthy individuals who were in home quarantine in April 2020 for at least one month participated in this study. Participants rated and compared their quantitative sleep parameters (time to go to bed, sleep duration, getting-up time) and sleep quality factors, pre-and during home quarantine due to the COVID-19 pandemic. Furthermore, participants’ chronotype was determined to see if sleep parameters are differentially affected in different chronotypes. Time to fall asleep and get-up in the morning were significantly delayed in all participants, indicating a significant circadian misalignment. Sleep quality was reported to be significantly poorer in all participants and chronotypes. Poor sleep quality included more daily disturbances (more sleep disturbances, higher daily dysfunctions due to low quality of sleep) and less perceived sleep quality (lower subjective sleep quality, longer time taken to fall asleep at night, more use of sleep medication for improving sleep quality) during home quarantine. Home quarantine due to COVID-19 pandemic has a detrimental impact on sleep quality. Online interventions including self-help sleep programs, stress management, relaxation practices, stimulus control, sleep hygiene, and mindfulness training are available interventions in the current situation.
EXCLI Journal;Vol. 19. 2020, pp.1297-1308
Keywords: COVID-19; Circadian misalignment; Chronotype; Quarantine; Lifestyle; Sleep; 610